Macro indicators in the engineering of the Islamic financial system - Alavi Seyyed Taleb (Kom: Časopis za Religijske Nauke)
Islamic and conventional financial systems have different ethical and philosophical foundations. While the traditional system relies on materialism, the Islamic system is based on theism. Therefore, it is crucial to localize and engineer a comprehensive model of the financial system based on macro indicators of the Islamic Financial system. This article intends to identify the macro indicators of the engineering of the Islamic Financial System from the content of authentic Islamic sources using Content Analysis methodology. The findings of this research indicate that certain indicators such as "freedom from usury", "Profit and Loss Sharing" (PLS), "distributive justice", "efficiency", and "governance of ethical virtues", should be regarded as important indicators in the engineering of Islamic financial system. These indicators are derived from the foundations and doctrines of Islam and the explicit content of religious ideas. Regarding the first index (freedom from usury), the Quran contains perspicuous commandments indicating that the secret of humankind's material felicity lies behind the elimination and avoidance of usury. By eliminating usury, the Islamic financial system based on PLS prioritizes fair profit distribution, negating predetermined and guaranteed positive returns. The indicator of "distributive justice" has been derived from an analysis of the position and characteristics of property in Islamic doctrine. "Efficiency" is rooted in the Islamic perspective, which includes wise use of property. Finally, ethics is one of the dynamic dimensions in the mission of the Holy Prophet of Islam. These five major indicators are compatible with the Islamic financial system's objective. However, if a conflict of indicators occurs in practice, the rational rule is to prefer the most important expediency to the important. This article outlines the criteria for distinguishing the most important from the important.